Effects of rainfall infiltration and hysteresis on the settlement of shallow foundations in unsaturated soil - Jeong, Sangseom (2020)
The effects of rainfall infiltration and hysteresis on the settlement of shallow foundations in unsaturated soil were numerically investigated. Numerical solutions were verified against experimental data. Rainfall intensities and groundwater table positions, factors that contribute to an additional settlement of shallow foundations, were investigated through a series of parametric studies. The effect of hysteresis on the settlement behavior of shallow foundations was considered by incorporating hysteretic soil–water characteristic curves (SWCC) that were obtained from the laboratory. A Reasonably good agreement of load-settlement response and matric suction distribution was obtained between the numerical analysis results and the field measurements. The parametric study showed that a reduction of matric suction due to rainfall infiltration induced the additional settlement of shallow foundations in unsaturated soil. The groundwater table position appeared to affect the wetting-induced settlement during rainfall due to the changes in matric suction. In addition, wetting SWCC analysis produced a slight larger settlement, up to 5% more than that produced by drying SWCC. Therefore, appropriate SWCCs (i.e., drying or wetting) should be used in numerical analysis in accordance with the conditions of the soils underneath the shallow foundations.